KONSTRUKSI MAKNA KEBEBASAN WANITA PADA IKLAN TRI (3) DI TELEVISI - Reko Aditia; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Ad Tri (3) version of women's liberation is an advertisement with the theme of freedom that elevates the social reality of women's lives in Indonesia as a people who demand freedom without having to be limited by stereotypes and gender roles, which do not get the freedom and the absence of equality of rights between men and women who eventually lead to gender equality. The purpose of the study is to determine and analyze the construction of the meaning of freedom of women in advertising Tri (3) on television.This research uses qualitative method based on Charles Sandrs Peirce Semiotic analysis model and based on primary data and secondary data. The technique of data validity uses triangulasi that is comparing the documentation data to the result of the research observation.The results of this research found that, freedom of women on advertising Tri (3) covers two aspects, those are, gender equality and prejudice, which were found by Peirce’s semiotic analysis model, and the construction of the meaning of freedom of women in advertising Tri (3) on television persuades and presents the attitude changing of the audience, especially the people of Indonesia to change negative views of women and accept their rights as a form of freedom.Keyword: Semiotic Analysis, Advertisement Tri (3), Freedom of Women